THE LINGUOCULTUROLOGICAL SIGNIFICANCE OF THE “PARENT” CONCEPT AND ITS REFLECTION IN WORLD LANGUAGES (ON THE EXAMPLE OF UZBEK, RUSSIAN, AND ENGLISH LANGUAGES) - Abdimurodov Doston Dilmurod Ugli (Scholar Express Journal, 2025)
This article explores the linguoculturological significance of the concept «parent» – encompassing both «mother» and «father»—and the ways it is verbalized in Uzbek, Russian, and English languages. Through a comparative analysis of proverbs, idioms, metaphors, and culturally-bound expressions, the study reveals how each language encodes societal values, moral norms, and emotional attitudes toward parental figures. The research applies the methods of conceptual analysis, cultural linguistics, and discourse analysis to identify universal and culture-specific features. The findings highlight how the alloconcept of “parent” serves as a cognitive-linguistic bridge between language and culture, contributing to the formation of national identity and intercultural understanding.
Keywords: concept; alloconcept; parenthood